2020
DOI: 10.18393/ejss.663486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium levels on teff (Eragrostis tef (Zucc.) Trotter) growth and yield in Central Highland Vertisols of Ethiopia

Abstract: Nutrient depletion and imbalance are among the major attributes that contribute to declining soil productivity in the highlands of Ethiopia. The blanket fertilizer recommendation, which considered only urea and Di-ammonium phosphate (DAP), was used over the past four decades to improve soil fertility for enhancing crop production. Nevertheless, the average national yields of small cereal including teff were low, despite application of nitrogen and phosphorus (NP) fertilizers. On-farm trials were conducted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…Furthermore, maximum yield was observed at a much higher vegetative K concentration in our experiment (1%) compared to the 0.63% K reported by Mulugeta et al [9] as the internal K requirement of tef. It is possible that the decreased grain yield in high K treatments reported by Mulugeta et al [9] was not caused by the increase in K itself, but rather a secondary effect caused by an imbalance of other nutrients. In our experiment, all other nutrients were provided at high rates and in available forms, so imbalances of other nutrients did not occur.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…Furthermore, maximum yield was observed at a much higher vegetative K concentration in our experiment (1%) compared to the 0.63% K reported by Mulugeta et al [9] as the internal K requirement of tef. It is possible that the decreased grain yield in high K treatments reported by Mulugeta et al [9] was not caused by the increase in K itself, but rather a secondary effect caused by an imbalance of other nutrients. In our experiment, all other nutrients were provided at high rates and in available forms, so imbalances of other nutrients did not occur.…”
Section: Discussioncontrasting
confidence: 59%
“…They reported yield rising and then plateauing with increased K, with a slight, non-significant drop at the highest K level. It is interesting that no decline in grain yield occurred in the higher K treatments, since Mulugeta et al [9] found a decline in grain yield in plants with much lower shoot K concentrations (0.6-0.9%) than the concentrations we measured in the highest K fertilization treatments (Figure 2C). Furthermore, maximum yield was observed at a much higher vegetative K concentration in our experiment (1%) compared to the 0.63% K reported by Mulugeta et al [9] as the internal K requirement of tef.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations